A Multidimensional Approach to Assessing Anthropometric and Aerobic Fitness Profiles of Elite Brazilian Endurance Athletes and Military Personnel. Issue 11 (3rd April 2019) - Xavier, Raphael; Sánchez, Carlos; Paulucio, Dailson; da Silva, Izadora Moreira; Velasque, Rodolfo; Nogueira, Fernando S; Ferrini, Luiz S G; Dornelas Ribeiro, Marcos; Serrato, Mauricio; Alvarenga, Renato; Pompeu, Fernando A M S; Santos, Caleb G M
Abstract: Introduction: Military personnel must remain physically active to meet operational requirements. Military physical training not only provides the performance capabilities required for performing occupational tasks but also fosters the development of sport. Thus, Armed Forces across the world have historically invested in developing elite- and Olympic-level athletes. This study aimed to assess the anthropometric and physiological differences among groups of Brazilian military athletes (MA), non-military athletes (A), and military non-athletes (M). Materials and Methods: Seventy-five individuals participated in the study: 17 MA (23.7 ± 4.8 years), 27 A (24.7 ± 5.3 years), and 31 M (26.9 ± 3.3 years). MA and A individuals specialized in endurance sports, and had a mean weekly training volume of (100.0 ± 34.8 and 106.3 ± 40.5 Km; F = 0.894, p = 0.6), respectively. Anthropometric measures and maximal oxygen uptake ( V ̇ O 2 m á x ) were assessed in all participants. Ergospirometry and anthropometry variables were analyzed with one-way analysis of variance (ANOVA) for independent measures. Comparisons of weekly training volume (km) and training experience (years) were performed only between the A and MA using the Student's t- test for independent samples. For a multidimensional approach, Partial least squares discriminant analysis (PLS-DA) was performed for all variables using the online tool MetaboAnalyst. Results: We found no differences in anthropometric and physiological profiles between A and MA, but significant differences between M and MA/A in body mass index (kg/m 2 ) (BMI), body fat percentage, fat mass (kg), waist circumference (cm) (WC), somatotype, and V ̇ O 2 m á x (mL min −1 kg −1 ). Conclusion: In conclusion, military endurance athletes have similar anthropometric and physiological profiles to non-military athletes and superior levels to non-athlete military. These findings indicate that the Brazilian Armed Forces scouting system has been successful in identifying endurance athletic talent in line with their historic role of developing sport in Brazil.